2020
DOI: 10.1002/ijc.33417
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive trends in incidence, treatment, survival and mortality of first primary invasive breast cancer stratified by age, stage and receptor subtype in the Netherlands between 1989 and 2017

Abstract: Our study aimed to provide a comprehensive overview of trends in incidence, survival, mortality and treatment of first primary invasive breast cancer (BC), according to age, stage and receptor subtype in the Netherlands between 1989 and 2017. Data from all women diagnosed with first primary stage I to IV BC (N = 320 249) were obtained from the Netherlands Cancer Registry. BC mortality and general population data were retrieved from Statistics Netherlands. Age‐standardised incidence and mortality rates were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 46 publications
4
24
0
Order By: Relevance
“…Relevant to consider is the median age at early breast cancer diagnosis, which is about 61 years. 12 We observed that 51% of patients were diagnosed with distant metastases more than five and 28% more than ten years after primary HR+/HER2− diagnosis, which also explains an elderly age at ABC diagnosis. In comparison to other cohorts, the EU-5 cohort with 82,073 patients diagnosed with HR+/HER2− ABC in 2008–2010 reported 37% of patients aged above 70 years, identical to our results (i.e.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Relevant to consider is the median age at early breast cancer diagnosis, which is about 61 years. 12 We observed that 51% of patients were diagnosed with distant metastases more than five and 28% more than ten years after primary HR+/HER2− diagnosis, which also explains an elderly age at ABC diagnosis. In comparison to other cohorts, the EU-5 cohort with 82,073 patients diagnosed with HR+/HER2− ABC in 2008–2010 reported 37% of patients aged above 70 years, identical to our results (i.e.…”
Section: Discussionmentioning
confidence: 70%
“…Obviously, the intensified early breast cancer treatment has led to a significant reduction in risk of recurrence and a better relative survival for patients diagnosed with early breast cancer. 12 , 13 , 14 But, for those who yet face a distant recurrence during follow-up, these shifts in the early breast cancer treatments may have changed the ABC patient baseline characteristics and may have worsened prognosis at time of ABC diagnosis. Conversely, the increased use of CDK4/6 inhibitors in daily practice is expected to lead to an improved overall survival for patients diagnosed with ABC since 2017.…”
Section: Introductionmentioning
confidence: 99%
“…We used incidence statistics of patients with breast cancer from the Netherlands Cancer Registry as a starting point. We then calculated the number of patients with HR-positive and ERBB2negative metastatic breast cancer per treatment line by applying proportions that were obtained from the literature [18][19][20][21][22][23] (ie, mainly a Dutch cohort study 21 ; Table 2) (eAppendix 3 and eFigure 2 in Supplement 1). In the Netherlands, the recommendation is to prescribe CDK4/6 inhibitors in the second line of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Breast screening is the only way to detect early breast cancer. Therefore, it is essential for women, especially those over 40 years, to undergo it periodically even if they have no symptoms [2,5,6]. Several methods are available for breast imaging, such as mammography, ultrasound (US), magnetic resonance imaging (MRI), computed tomography (CT), positron emission tomography (PET), and microwave imaging [7].…”
Section: Discussionmentioning
confidence: 99%